STUDI KOMPARASI KADAR GLUKOSA PADA NASI YANG DIMASAK DENGAN METODE RICE COOKER DAN DENGAN METODE TRADISIONAL PADA BERBAGAI SUHU - Juwita, Linda (Journal of Nursing Care and Biomoleculer, 2020)
Introduction: differences in how to cook and process food will cause different glucose responses. The process of cooking or heating will cause the gelatinization process in starch so that starch will be more easily digested because the digestive enzymes in the intestine get a wider workplace. Particle size also affects the glycemic index. The smaller particle size causes the structure of food to be smooth so that the food is easily digested and absorbed in the body and causes blood sugar levels to rise rapidly. The purpose of this study is to explain glucose levels in cooked rice with the Teflon rice cooker method, stainless rice cooker and with the traditional / steaming method at various temperatures. Methods: Glucose levels were determined by the dinitrosalicylic acid method, spectrophotometric-colorimetric methods using cooked rice with various methods (Teflon rice cookers, steamed and stainless rice cookers) and various temperatures (hot, warm and cold). each sample was repeated three times. Data were tested using a statistical test with SPSS 20 with a Randomized Group Design test (RCBD). Results and Analysis: p <0.05 which means that there are significant differences in glucose levels with various methods and varying temperatures, but in the Post Hoc Test did not get the lowest recommendation of rice glucose levels. Each method of cooking rice will have a different cooking temperature so that there will be a process of changing the content of rice during the cooking and heating process. the real difference in glucose levels in the results of this study is due to differences in temperature in the cooking process so that the leaching process occurs, then the temperature difference when tested causes the starch retrogradation process, so that the interaction of various methods and the temperature of rice produces differences in rice glucose levels.